2023
DOI: 10.3390/ijms242015321
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Biomarkers for Immunotherapy in Gastric Cancer: Current Status and Emerging Prospects

Wanting Hou,
Yaqin Zhao,
Hong Zhu

Abstract: Gastric cancer presents substantial management challenges, and the advent of immunotherapy has ignited renewed hope among patients. Nevertheless, a significant proportion of patients do not respond to immunotherapy, and adverse events associated with immunotherapy also occur on occasion, underscoring the imperative to identify suitable candidates for treatment. Several biomarkers, including programmed death ligand-1 expression, tumor mutation burden, mismatch repair status, Epstein–Barr Virus infection, circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Also, Chen et al confirmed the role of the TIL signature found through mIHC and multi-dimensional analyses in foreseeing anti-PD-1/PD-L1 responsiveness [ 33 , 40 ].…”
Section: Immunotherapy and Biomarkers: Classical Perspectivementioning
confidence: 93%
See 1 more Smart Citation
“…Also, Chen et al confirmed the role of the TIL signature found through mIHC and multi-dimensional analyses in foreseeing anti-PD-1/PD-L1 responsiveness [ 33 , 40 ].…”
Section: Immunotherapy and Biomarkers: Classical Perspectivementioning
confidence: 93%
“…TPS represents the percentage of tumor cells stained with any intensity of PD-L1, while CPS accounts for PD-L1-positive tumor cells and tumor-associated immune cells divided by the total number of tumor cells. Moreover, the analysis of the PD-L1 expression in circulating tumor RNA (ctRNA) conducted by Ishida et al suggested the utility of ctRNA for predicting and monitoring immunotherapy responsiveness [ 32 , 33 ].…”
Section: Immunotherapy and Biomarkers: Classical Perspectivementioning
confidence: 99%
“…Gastric cancer is the fourth leading cause of cancer-related deaths worldwide [1]. Research into various biomarkers [2,3] and immune-related treatments [4,5] is ongoing to improve early diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%